# In ∆Abc, Prove that If θ Be Any Angle, Then B Cosθ = C Cos (A − θ) + a Cos (C + θ). - Mathematics

In ∆ABC, prove that if θ be any angle, then b cosθ = c cos (A − θ) + a cos (C + θ).

#### Solution

Suppose

$\frac{a}{\sin A} = \frac{b}{\sin B} = \frac{c}{\sin C} = k$  ...(1)

Consider the RHS of the equation b cosθ = c cos (A − θ) + a cos (C + θ).

$RHS = c\cos\left( A - \theta \right) + a\cos\left( C + \theta \right)$

$= k\sin C\cos\left( A - \theta \right) + k\sin A\cos\left( C + \theta \right) \left( from \left( 1 \right) \right)$

$= \frac{k}{2}\left[ 2\sin C\cos\left( A - \theta \right) + 2\sin A\cos\left( C + \theta \right) \right]$

$= \frac{k}{2}\left[ \sin\left( A + C - \theta \right) + \sin\left( C + \theta - A \right) + \sin\left( A + C + \theta \right) + \sin\left( A - C - \theta \right) \right]$

$= \frac{k}{2}\left( \sin\left( \pi - B - \theta \right) + \sin\left( C + \theta - A \right) + \sin\left( \pi - B + \theta \right) - \sin\left( C + \theta - A \right) \right) \left( \because A + B + C = \pi \right)$

$= \frac{k}{2}\left( \sin\left( B + \theta \right) + \sin\left( B - \theta \right) \right)$

$= \frac{k}{2}\left( \sin B\cos\theta + \sin\theta\cos B + \sin B\cos\theta - \sin\theta\cos B \right)$

$= \frac{k}{2}\left( 2\sin B\cos\theta \right)$

$= k\sin B\cos\theta$

$= b\cos\theta = LHS$

$\text{ Hence proved } .$

Concept: Sine and Cosine Formulae and Their Applications
Is there an error in this question or solution?

#### APPEARS IN

RD Sharma Class 11 Mathematics Textbook
Chapter 10 Sine and cosine formulae and their applications
Exercise 10.1 | Q 25 | Page 13